Remote Sensing and Precision Agriculture Technologies for Crop Disease Detection and Management with a Practical Application Example - Yang, Chenghai (Engineering (Beijing, China), 2020)
Remote sensing technology has long been used to detect and map crop diseases. Airborne and satellite imagery acquired during growing seasons can be used not only for early detection and within-season management of some crop diseases, but also for the control of recurring diseases in future seasons. With variable rate technology in precision agriculture, site-specific fungicide application can be made to infested areas if the disease is stable, although traditional uniform application is more appropriate for diseases that can spread rapidly across the field. This article provides a brief overview of remote sensing and precision agriculture technologies that have been used for crop disease detection and management. Specifically, the article illustrates how airborne and satellite imagery and variable rate technology have been used for detecting and mapping cotton root rot, a destructive soilborne fungal disease, in cotton fields and how site-specific fungicide application has been implemented using prescription maps derived from the imagery for effective control of the disease. The overview and methodologies presented in this article should provide researchers, extension personnel, growers, crop consultants, and farm equipment and chemical dealers with practical guidelines for remote sensing detection and effective management of some crop diseases.